Hijab Trend: Combining Religious Values And Modern Fashion - rahmaifa nasyah; Dea Ananda Wilianca; Ali Akbar (Yayasan Adra Karima Hubbi, 2024)
Background. The hijab has become a significant part of Muslim women's identity, reflecting both religious values and cultural trends. It embodies a blend of tradition and modernity, presenting a complex interplay between spirituality and self-expression. Purpose. This journal explores the hijab's definition, historical development, and scholarly perspectives, particularly its evolving role in contemporary fashion. The objective is to understand how the hijab functions as both a religious obligation and a medium of self-expression. Method. Using a qualitative research method with a literature-based approach, this study analyzes Qur’anic verses such as Surah An-Nur and Surah Al-Ahzab alongside scholarly interpretations. Data were collected from academic texts and studies focusing on the hijab's cultural and spiritual significance. Results. The findings reveal that the hijab has transitioned beyond its traditional role as a religious obligation to become a versatile accessory in the fashion industry. Society now embraces the hijab as a cultural statement that balances faith and personal style, illustrating its dual function as both a spiritual symbol and a cultural trend. Conclusion. This study concludes that the hijab serves as a bridge between Islamic principles and modern fashion, offering Muslim women a unique space to express their identity while adhering to religious commitments. By examining the hijab in this broader context, the research highlights its dynamic role in shaping contemporary cultural and social narratives.